BPOM Regulations and Responsibilities in The Case of Medicines Containing Ethylene Glycol And Diethylene Glycol - Devi Silvia; Tiurma Mangihut Pitta Allagan (Green Publisher Indonesia, 2024)
This study aims to find out two problems, namely how is the regulation, role and responsibility of BPOM in the case of drugs containing EG and DEG?; and how is BPOM's responsibility for the legal protection of consumers who consume these drugs? To answer this, researchers apply normative legal studies with secondary data and use qualitative analysis with deductive thinking to draw conclusions. The results of the study stated that there is a legal vacuum in the regulation of BPOM where there is no regulation regarding sanctions if BPOM issues a distribution permit for dangerous products. The role of BPOM in the case of the circulation of drugs containing EG and DEG is in accordance with its function as a product supervisor either before or after circulation, imposing sanctions on business actors, namely revoking distribution permits for harmful products as its authority is regulated in PP 80 of 2017. Preventive legal protection is not implemented properly by BPOM while repressive protection is carried out by reporting and participating in investigations with the police, business actors who distribute drugs with these ingredients.